Evaluasi Tata Kelola Teknologi Informasi Pada Dinas Komunikasi dan Informatika (Dinkominfo) Kabupaten Bojonegoro Menggunakan Framework COBIT 4.1 Fokus Domain Plan and Organise (PO) dan Acquire and Implement (AI) - Sandy Rastra Sewakottama; Yusi Tyroni Mursityo; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Dinkominfo of Bojonegoro Regency is a government institution that focuses of Information and techonology (IT) sector. There are two divisions in the sector, namely E-Government services and Communication IT field. The utilization The utilization of IT, nowadays, is essential in government area. For a good IT utilization, well-arranged IT governance is needed, as for the utilization of IT is able to reach the implementation of Dinkominfo in line with its vision, mission, goals, and business process. Based on the interviews, Dinkominfo of Bojonegoro Regency has several problems, such as its on-going IT investments have not been in accordance with the benefits obtained, application and operational maintenance, and IT utilization does not have specific planning. Therefore, the purpose of this study is to find out the maturity level of IT governance at Dinkominfo of Bojonegoro Regency with framework of COBIT 4.1 PO (Plan and Organise) and AI (Acquire and Implement) domains. The results of the research conducted, can be known the average value of Maturity Level in each domain, the PO domain process is 1.60 and the AI domain process is 1.28. In order to increase the maturity level value of the current maturity level with the expected maturity level. Several recommendations were given that could increase the maturity level value of the current maturity level with the expected maturity level. Examples of recommendations are generated such as defining and documenting related risk management at the time of implementing IT and training IT resources at Dinkominfo of Bojonegoro Regency.